Estimation of magnitude of heterosis for growth traits in onion (Allium cepa) (Current Horticulture, 2024)
The experiment was conducted to estimate the magnitude of heterosis for growth traits in onion (Allium cepa L.) for 28 F1s crosses  at SKN College of Agriculture, Jobner, Rajasthan. These genotypes were planted in randomized block design with three replications  under 3 date of sowing during rabi season,2022-23. The most heterotic crosses for growth contributing characters were RO-59 ×  Bhima Shakti, Pusa Shobha × Pusa Red, Bhima Shakti × Pusa Shobha RO-59 × Pusa Shobha, Kashi No. 1 × Pusa Red and RO-1 ×  Pusa Red. The crosses had significant heterobeltiosis for growth contributing characters RO-59 × Bhima Shakti, Bhima Shakti ×  Pusa Shobha, Pusa Shobha × Pusa Red RO-1 × Kashi No. 1, RO-1 × RO-59 and RO-1 × Pusa Madhavi. These crosses were considered  promising for their use for growth improvement in onion.
Keywords: Heterosis; Growth; Heterobeltiosis; Crosses; Improvement